Tradisi Keilmuan Pesantren dalam Membentuk Peradaban Islam Indonesia - Apriyanto Purwa Setiyawan; Zufar Athif Hanifudien; Ikhsan Aji Pamungkas; Afif Ashim Syahrul (Jurnal Pendidikan dan Sastra Inggris, 2026)
Pesantren (Islamic boarding schools) as the oldest and most authentic Islamic educational institution in Indonesia play a central role not only as transmitters of religious knowledge but also as shapers of Islamic civilization in the archipelago. This qualitative case study at Pesantren Tremas and Pesantren Langitan aims to examine the scholarly tradition of pesantren, which is built upon the foundations of sanad (chain of transmission), the study of classical Islamic texts (kitab kuning), and the bandongan and sorogan learning methods, as well as its contribution to framing a moderate Indonesian Islamic civilization. The research findings indicate that this scholarly tradition successfully forms a distinct epistemology and intellectual habitus, producing a synthesis between the authenticity of tradition (al-muhafazhah ‘ala al-qadim al-shalih) and adaptation to modernity (al-akhdzu bi al-jadid al-aslah) through the integration of religious (naqliyah) and general/scientific (kauniyah) sciences. Tangible contributions are manifested in the preservation of classical Islamic heritage, the reproduction of networks of moderate Islamic scholars, the indigenization of Islamic values, and the instillation of social ethics that uphold harmony. Although faced with challenges of digitalization and educational competition, the adaptive capacity of pesantren through methodological revitalization and the digitalization of classical texts. ensures the continuity of its role as a laboratory and dynamist for a character-driven Indonesian Islamic civilization.